The principles of beautiful web design - Beaird, Jason (Collingwood, Australia : Sitepoint, 2010)
This volume leads readers through the process of creating Web page designs from start to finish, while explaining what makes "good design". The author presents topics such as developing pleasing layouts using grids, the rule of thirds, balance and symmetry, using color effectively, developing color schemes and creating a palette, using textures, lines, points, shapes, volumes and depth among many other useful lessons.
1. Layout and composition. The design process -- Defining good design -- Web page anatomy -- Grid theory -- Balance -- Unity -- Emphasis -- Bread-and-butter layouts -- Finding inspiration -- Fresh trends -- Resizing : fixed, fluid, or responsive layouts -- Screen resolution -- Application : Southern savers -- 2. Color. The psychology of color -- Color temperature -- Chromatic value -- Color theory 101 -- Red, yellow, and blue or CMYK -- The scheme of things -- Creating a palette -- Color tools and resources -- Application : the color of coupons -- 3. Texture. Point -- Line -- Shape -- Volume and depth -- Pattern -- Building texture -- Application : clipping and saving -- 4. Typography. Taking type to the web -- Text image replacement -- Web fonts with @font-face -- Anatomy of a letterform -- Text spacing -- Text alignment -- Typeface distinctions -- Finding fonts -- Choosing the right fonts -- Application : The fine print -- 5. Imagery. What to look for -- Legitimate image sources -- Getting professional help -- How not to impress -- Creative cropping -- Photoshop adjustments -- File formates and resolutions -- Creative image treatments -- Application : The fine print -- Onward and upward.
Includes index.
Keywords: WEB SITES -- DESIGN